Implementation of the Importance of Using Manual Material Handling (MMH) Trolley for Load Transportation Based On Ergonomic In Ikm Desa Bangun Sari Kec. Kampar Kiri Hilir - Kumala Sari, Resy; Setiawan, Beny; Yusmita, Yesi; Hardianti, Sri; Syifa Tanjung, Lailatul (Journal of Social and Community Service, 2022)
IKM workers in Bangun Sari Village, Kec. Kampar Kiri Hilir still uses human power when lifting weights, this causes Musculoskeletal Disorders (WMSDs) such as back pain, injuries to muscles, nerves, tendons, bones, joints, cartilage, and other body aches. This can cause losses to SMEs, one of which is a decrease in the level of worker productivity and a decrease in the low level of production. With the Implementation of the Importance of Using Manual Material Handling (MMH) Trolleys for Ergonomics-Based Load Transportation at IKM Desa Bangun Sari Kec. Lower Left Kampar. The service method is carried out at IKM Desa Bangun Sari Kec. Kampar Kiri Hilir, and was attended by 16 workers and Small and Medium Industry owners. The socialization was held for 1 meeting in June 2022. The result of this socialization was to increase knowledge about health in lifting weights with a safe posture. education on the importance of using the Manual Material Handling (MMH) Trolley in transportation and lifting loads for SMI workers to reduce injury to the body. Empowerment of IKM owners and related people in monitoring the use of trolleys is expected to be realized properly by providing several examples of using trolleys properly and correctly so as to create a comfortable and safe position.